2022
DOI: 10.1021/acsaelm.2c00311
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Approach to Achieving Ultrasmall III-Nitride Microlight-Emitting Diodes with Red Emission

Abstract: The microdisplays for augmented reality and virtual reality require ultrasmall micro light-emitting-diodes (μLEDs) with a dimension of ≤5 μm. Furthermore, the microdisplays also need three kinds of such μLEDs each emitting red, green, and blue emission. Currently, in addition to a great challenge for achieving ultrasmall μLEDs mainly based on III-nitride semiconductors, another fundamental barrier is due to an extreme difficulty in growing III-nitride-based red LEDs. So far, there has not been any effective ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Multi-color pixels and micron-scale platelets, pyramids, nanowires were reported by Kishino et al's studies [302]. Recent research by Wang et al [303], [37,304]however, demonstrated green LED matrices with a peak EQE of ~9% and red-emitting micro-LEDs with a peak EQE of 1.75%, both grown utilising selective area epitaxy [37,304]. For instance, an integration between a micro-LED and a high-electron-mobility-transistor (HEMT) resulted in a modulation bandwidth of 1.2 GHz, which is the highest ever recorded in this context [305].…”
Section: Photolithography and Photoresistmentioning
confidence: 85%
See 1 more Smart Citation
“…Multi-color pixels and micron-scale platelets, pyramids, nanowires were reported by Kishino et al's studies [302]. Recent research by Wang et al [303], [37,304]however, demonstrated green LED matrices with a peak EQE of ~9% and red-emitting micro-LEDs with a peak EQE of 1.75%, both grown utilising selective area epitaxy [37,304]. For instance, an integration between a micro-LED and a high-electron-mobility-transistor (HEMT) resulted in a modulation bandwidth of 1.2 GHz, which is the highest ever recorded in this context [305].…”
Section: Photolithography and Photoresistmentioning
confidence: 85%
“…Reduced quantum efficiency due to crystal defects like dislocations in III-nitride nanostructures underscores the need for defect mitigation to improve crystal quality. Improved growth techniques are required to reduce defects while enhancing the structural integrity of III-nitride nanostructures [304,337]. In spite of these hurdles, III-nitride nanostructures, especially gallium nitride (GaN), hold great promise across various applications [338].…”
Section: Commercialisation Challenges and Applications Of Micro-led D...mentioning
confidence: 99%
“…Based on the CSE approach, ultrasmall µLEDs with a record EQE in the green and red spectral regions have been achieved [98,99]. The CSE approach has also led to the demonstration of epitaxially integrating a microcavity and ultrasmall µLEDs achieving a very stable emission wavelength and the demonstration of monolithically integrating µLEDs with HEMTs for VLC and microdisplay applications [100][101][102][103].…”
Section: Advances In Science and Technology To Meet Challengesmentioning
confidence: 99%
“…Based on our CSE approach, the Sheffield team has achieved ultra-small µLEDs without involving dry-etching processes, leading to the demonstration of ultra-small and ultra-compact µLEDs with a record EQE and small reverse leakage current in the green and red spectral regions. [33,34,36,37] Based on this CSE approach, by epitaxially integrating a microcavity and ultra-small µLEDs, ultrasmall and ultra-compact µLEDs with a stabilized emission wavelength have been achieved, [35] which is extremely important for practical applications and has addressed the longstanding issue in the field of III-nitride optoelectronics. In addition, the CSE approach has also been employed to monolithically integrate µLEDs with high electron mobility transistors (HEMTs) for visible light communication (VLC) and display applications.…”
Section: Nature and Mechanism Of The Confined Selective Epitaxy Approachmentioning
confidence: 99%
“…In our di-rect epitaxial approach, µLEDs are grown in the regularly arrayed micro-holes, naturally forming relaxation in the lateral direction and thus enhancing indium incorporation into GaN. Using regularly arrayed micro-hole masks (namely, 2 µm diameter and 1.5 µm-spacing), red µLEDs with an emission wavelength at 642 nm and a peak EQE of 1.75% have been achieved, [36] as shown in Fig. 4.…”
Section: Demonstration Of Red µLeds Due To Enhanced Indium Incorporationmentioning
confidence: 99%